2019
DOI: 10.3390/diagnostics9030095
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Classified as Untestable on Brief Cognitive Screens in an Acute Stroke Setting?

Abstract: Full completion of cognitive screening tests can be problematic in the context of a stroke. Our aim was to examine the completion of various brief cognitive screens and explore reasons for untestability. Data were collected from consecutive stroke admissions (May 2016–August 2018). The cognitive assessment was attempted during the first week of admission. Patients were classified as partially untestable (≥1 test item was incomplete) and fully untestable (where assessment was not attempted, and/or no questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…This clinical practice, data-based study showed that 44% of the patients did not undergo cognitive screening during their stay in ASUs. The proportion of unscreened patients is higher than those reported by other studies, where approximately 17% of the patients did not undergo cognitive screening 10 , 25 . The divergence between the results of the present and previous studies may be related to the study design.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This clinical practice, data-based study showed that 44% of the patients did not undergo cognitive screening during their stay in ASUs. The proportion of unscreened patients is higher than those reported by other studies, where approximately 17% of the patients did not undergo cognitive screening 10 , 25 . The divergence between the results of the present and previous studies may be related to the study design.…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, the registry datasets generated from clinical practice were used. Thus, a more representative picture of clinical practice could be described compared with that in other studies where data collection was conducted with pre-specified inclusion and exclusion criteria 10 , 25 . Therefore, the results might be representative of other stroke units.…”
Section: Discussionmentioning
confidence: 99%
“…[42]. The specific tasks included in this measure have been described in a previous publication [43].…”
Section: Mediatorsmentioning
confidence: 99%
“…Common themes from our PROBAST ratings highlight some of the challenges inherent to stroke prognostic research. Stroke-related impairments limiting completion of certain assessments, 28 deaths and losses to follow-up can all contribute to missing data and biased study samples. Another challenge relates to incorporation bias, where the assessment of the outcome of interest requires knowledge of factors that inform the prognostic tool.…”
Section: Discussionmentioning
confidence: 99%